2023
DOI: 10.1093/eurjpc/zwad275
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of pre- and post-natal target organ damage associated with hypertensive pregnancy: a systematic review

Hannah Rebecca Cutler,
Logan Barr,
Prenali Dwisthi Sattwika
et al.

Abstract: Aims Hypertensive pregnancy is associated with increased risks of developing a range of vascular disorders in later life. Understanding when hypertensive target organ damage first emerges could guide optimal timing of preventive interventions. This review identifies evidence of hypertensive target organ damage across cardiac, vascular, cerebral, and renal systems at different time points from pregnancy to postpartum. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…In recent years, it has become increasingly recognized that preeclamptic women undergo significant cardiac remodeling, mainly assessed using echocardiography. 8 Hall et al demonstrated preeclamptic women had higher left ventricular mass and a unique 3-dimensional cardiac shape, including eccentric remodeling and outflow tract changes. Higher left ventricular mass has also been observed in women 5 to 10 years after preeclamptic pregnancies using MRI and creation of a 3-dimensional computational atlas.…”
Section: Insights Into the Pathophysiology Of Preeclampsiamentioning
confidence: 99%
“…In recent years, it has become increasingly recognized that preeclamptic women undergo significant cardiac remodeling, mainly assessed using echocardiography. 8 Hall et al demonstrated preeclamptic women had higher left ventricular mass and a unique 3-dimensional cardiac shape, including eccentric remodeling and outflow tract changes. Higher left ventricular mass has also been observed in women 5 to 10 years after preeclamptic pregnancies using MRI and creation of a 3-dimensional computational atlas.…”
Section: Insights Into the Pathophysiology Of Preeclampsiamentioning
confidence: 99%